Variabilidade da metilação do DNA em gêmeos - Estorgato, Geovana Rhoden (2020)
Introduction: DNA methylation variability can begin in the early stages of development, continue throughout the gestational period, and remain throughout life. Objective: Systematically review the literature on DNA methylation variability patterns throughout life in twins. Methods: a systematic search was conducted in the MEDLINE, EMBASE, The Cochrane Controlled Trials Register, Scientific Electronic Library Online, Latin American Caribbean Health Sciences Literature, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, Web of Science and literature databases gray; without date or language limit, in order to characterize DNA methylation variability throughout life in twins. The PECO strategy was defined, in which the study participants were twins of any age; exposure was age throughout life; there was no comparison to any other exposure; and the outcome was the DNA methylation variability. The quality of the studies was analyzed according to the Checklist Downs and Black. Results: Nine articles with a total of 6,078 individuals, comprising 1,536 monozygotic twin pairs and 1,066 dizygotic twin pairs, were included. The age range of the participants varied from 0 to 89 years. There were different changes in DNA methylation throughout life, such as increased/decreased/stable global methylation patterns, as well as distinct methylation changes of individual genes over time. A quantitative analysis of results from six studies determined that the mean estimate of proportion variance overtime was 27.84% (range: 3.2% - 103.2%). Overall, the variance was higher among twins older than ten years old compared to twins younger than ten years old. Conclusion: This systematic review suggests that temporal DNA methylation patterns vary between twins throughout life and generally increase in variance with age.